Risk Management of Cash Withdrawal Services through Fintech Friends among Gen Z: Manajemen Risiko Layanan Tarik Tunai Melalui Teman Fintech di Kalangan Gen Z - Hani, Fildzah; Sugianto, Sugianto; Nasution, Muhammad Irwan Padli (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The increasing adoption of fintech applications among younger demographics has transformed the landscape of financial transactions, particularly with the introduction of peer-assisted features such as Teman. Specific Background: Among Generation Z users, the convenience of digital cash withdrawal services often overshadows the underlying risks, posing challenges to both users and service providers. Knowledge Gap: However, limited research has explored the specific risk dynamics and mitigation strategies within such fintech-mediated services targeted at Gen Z. Aims: This study aims to analyze risk management in cash withdrawal services via the Teman feature in fintech apps, focusing on the types of risks encountered and the strategies employed to address them. Results: The findings reveal that fraud, personal data leakage, and account misuse are the primary risks, exacerbated by low levels of digital financial literacy among Gen Z users. Novelty: Employing a qualitative phenomenological approach, this research offers an in-depth understanding of user experiences and the nuanced risks in emerging fintech features. Implications: The study underscores the urgency of enhancing digital financial education and enforcing stricter regulatory measures to bolster security and trust in fintech ecosystems. Highlights: Highlights key risks in fintech cash withdrawal services used by Gen Z. Emphasizes the role of low digital financial literacy in increasing vulnerability. Recommends stronger regulation and targeted financial education efforts. Keywords: Risk Management, Fintech, Cash Withdrawal Services